Turunan Radial dari Anomali Gravitasi untuk Identifikasi Injeksi Air pada Reservoir - Zuhdi, Muhammad; Busyairi, Ahmad (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2024)
Time Lapse micro-gravity or 4D microgravity has been developed and applied for various purposes related to the dynamics change beneath the earth's surface. The principle is a repeated and periodic measurement to determine the change in gravity value at time interval as a yield of the dynamics changes in the density change of the subsurface. This method can be used for monitoring and identify water or gas injections in reservoirs. Mass density taht changes due to gas injection provide changes in the values of gravity over time. This change allows us to identify the dynamics of gas movement in reservoir. A reservoir model has been made in this research with gas injected in reservoir bulk. The time lapse gravity respons value is calculated numerically. Oil-gas contact is an edge between gas injection front with oil which move direction away from injection point. The first and second radial derivatives of 4D gravity can provide as a front of the gas movement in the reservoir. A radial derivatives is a horizontal derivative of gravity anomaly along radial direction from a point which selected as a entre of the anomaly. The second radial derivative is derivative of radial deriative. Radial derivatives value of this model response have range of 20 microGals/m and second radial derivative has a values of 0.05 microGals/m2. Graphics of absolute value of radial derivative and second radial derivative of 4D gravity anomaly seemingly correlated with the oil-gas contact of reservoir models. Radial derivative and second radial derivative has been proven as new available method wich has ability to shows a boundary of a horizontal layer with vertical density contrast. Keywords: Radial derivatives, reservoir, gas injection.